INSPECTION AS AN INSTRUMENT OF WATER RESOURCES MANAGEMENT IN THE STATE OF SAO PAULO - Silva, Isabela Redigolo da [UNESP]; Di Mauro, Claudio Antonio [UNESP] (Univ Federal Mato Grosso, 2021)
The supervision is an essential instrument to the implementation of national and state water resources policies. The aim of the present study was to comprehend the way how it is performed in the Sao Paulo state. To the realization of this research, the Basin Directorates of Peixe Paranapanema, Medio Tiete, and Ribeira do Iguape e Litoral Sul, components of Department of Water and Electric Energy (DAEE), were adopted as study areas. The used methodological resources were the exploratory and qualitativeresearch, associated withthe bibliographic and documental research, in addition to the half-structuredinterview. The results point that there are not settled patterns for the supervision actions of water resources use, that there are limiting difficulties and variations in the actions of the Basin Directorates; suggesting that the supervision occurs in a deficient manner in relation to what the state legislation establishes.
Keywords: SUPERVISION IN WATER RESOURCES; WATER BASINS; WATER BASINS PLANNING; WATER BASINS MANAGEMENT INSTRUMENTS